Diretores de escola: o que fazem e como aprendem - Mello, Márcia Maria de (2014)
This study aims to provide a broader understanding of the professional demands that characterize the jobs of school managers, by entering their environment and disclosing the sequence of events, as well as the configuration of contexts, situations, professional learning and professional development activities that constitute their daily routine. The study is founded on the school management principles stated by Lück (2009); the management profile of public schools and aspects of teacher performance described by Libâneo, Oliveira and Toschi (2007), and Souza (2007, 2008, 2009, 2010). The learning of teaching in Mizukami et al (2002) and Tancredi (2009); the work of Lortie (2009) with school principals of a Chicago suburban school.The methodological procedures were structured into four phases: the elaboration of a data-collecting instrument, the conducting of interviews, the creation of management activity logs and the categorization and analysis of collected data. The participants were six school principals working in the community school network of a city in Sao Paulo State, Brazil. Data categorization showed that the set of specific knowledge applied in the daily routine of school managers comes mainly from the professional practice itself rather than from the formal undergraduate education. It is therefore noticeable that the handling of practical situations and conflicts leads to the construction of an essential repertoire of skills that cannot be found at, or provided by, the undergraduate curricula that are supposed to develop such knowledge and skills prior to the exposure of these professionals to the managerial practice. This practical developmental process is particularly influenced by the presence of more experienced peers who help the less experienced in the acquisition of professional knowledge; the sharing of experiences among peers standing at the same career level; and the presence of an orientation program offered by the hiring network. The in-job experience also allows for the identification of training needs within the group investigated, whose members, in turn, claim for the filling of educational gaps and point out the need for intervention in the system where they are inserted.